Integrating Hawgent Dynamic Mathematics Software into Cone Volume Geometry Learning in Elementary School - Zou, Shuo; Tang, Jianlan; Pereira, Jerito (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2022)
The aim of this research is to integrate Hawgent dynamic mathematics software into geometry learning to help teachers explain concepts and students understand the basic concept of volume of cone in 6th grade of elementary school. The research was conducted at Ningcheng Third Experimental Primary School with the population being all 6th grade students of the 2021/2022 school year. Sampling with a cluster random sampling technique and selected 40 students of 6th grade as the sampling class. In this teaching experiment research, the researcher was using a BOPPPS model based on the APOS theory. The research results showed that 79.49% of the students agree that the integrating Hawgent dynamic mathematics software into cone volume geometry learning process can help them understand the concept of cone volume. Integrating Hawgent dynamic mathematics software improves their interest in learning, the basis of in-depth understanding of knowledge, and the accuracy of the problem. In addition, information, communication and technology is highly integrated with classroom teaching, which can enrich classroom content and improve learning efficiency.